DESIGNING THE VISUAL CHARACTER “LAKSAMANA MEGANTARA” AS A VISUAL REPRESENTATION OF INDONESIAN MARITIME CULTURE - Herdadi, Nadinti Salsabila; Prameswari, Nadia Sigi (LPPM Univ. Ibn Khaldun Bogor, 2025)
Indonesia is the largest archipelagic country in the world and is often referred to as a maritime nation. However, public awareness of maritime culture remains low, particularly among children and teenagers. This design project aimed to create a character design that represents Indonesian maritime culture. The writer employed a qualitative method combined with an iconographic approach, utilizing symbolic elements derived from books and articles that discuss maritime cultural elements, history, and iconography in Indonesia. This approach was chosen to simplify the design process, especially when direct observation was not possible due to limited access to sources. The findings from the literature served as the foundation for the character development. The resulting character represents Indonesian maritime culture, inspired by the Malay ethnic group from the Riau Islands. It is expected that this character design can raise public awareness—particularly among the younger generation—of the nation's rich maritime heritage as a form of respect, preservation, and wise utilization of the sea, while also strengthening the focus on maritime culture as part of national identity.